Not only Berlusconi: A Panoramic Overview of Italian Populists of the Second Republic in the Linguistic and Historical Context - Berezowski, Łukasz Jan (Populismo y propaganda: entre el presente y el pasado, 2020)
The article discusses the issue of populism and populists of the Italian political scene of the 2nd Republic. In the introductory part of the paper the author aims to provide an explanation of the term “populism” in both etymologic and semantic perspectives (from linguistic and historic view). Subsequently, a selected overview of Italian populists of the 2nd Republic shall be highlighted (as well as the term itself shall be made clear). They were chosen following a temporary criterion: among politicians who held public offices (ministers/members of Parliament/leaders of the governing and opposition parties) in the first decades after the Tangentopoli scandal and still take active part in public life. Their words coming out from their most popular speeches are confronted and analyzed in terms of language means applied to obtain the effect of shock, outrage or derision towards a political adversary. In conclusion, the function of message conveyed by a politician shall be emphasized, which differs depending on the model to be followed, not the ideological beliefs.